2009
DOI: 10.1007/s00384-009-0775-2
|View full text |Cite
|
Sign up to set email alerts
|

Anal cancer treated with radio-chemotherapy: correlation between length of treatment interruption and outcome

Abstract: Definitive radio-chemotherapy with short individualised treatment interruption shows high local control and colostomy-free survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Out of 130 papers, 116 papers reported all adverse events (regardless of grade), 14 papers reported only adverse events Grade 3 or above. The incidence of Grade 1 and 2 toxicities were 26.4-50%, whilst that of Grade 3 and above were reported to occur between 0 and 33.3% of patients [4,[20][21][22][23][24][25][26]. Eighteen papers reported only the incidence of overall GI adverse events with no data for individual GI symptom [4,[27][28][29][30].…”
Section: Overviewmentioning
confidence: 99%
“…Out of 130 papers, 116 papers reported all adverse events (regardless of grade), 14 papers reported only adverse events Grade 3 or above. The incidence of Grade 1 and 2 toxicities were 26.4-50%, whilst that of Grade 3 and above were reported to occur between 0 and 33.3% of patients [4,[20][21][22][23][24][25][26]. Eighteen papers reported only the incidence of overall GI adverse events with no data for individual GI symptom [4,[27][28][29][30].…”
Section: Overviewmentioning
confidence: 99%
“…84,85,86 However, a retrospective analysis of 101 patients treated with http://www.sajo.org.za Open Access chemoradiation demonstrated that a 5-year local control and colostomy-free survival rates were not adversely affected when treatment was interrupted by more than six cumulative treatment days, compared to six or less. 87…”
Section: Anus Overall Treatment Timementioning
confidence: 99%
“…As results matured and further insight in tumor radiobiology was gained, this long treatment gap was considered to be potentially hazardous, due to the likelihood of tumor repopulation during the treatment gap. In the subsequent studies, the treatment gap was shortened to 2 weeks, which not only seemed to be feasible, but also resulted in better LRC in some studies [36][37][38][39][40] but not in others [41,42]. With the advent of IMRT and VMAT, the entire radiation course could be administered without a treatment break.…”
Section: The Treatment Gapmentioning
confidence: 99%